2016
DOI: 10.1136/bmjopen-2015-009905
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pathways to breast cancer diagnosis among women in the Western Cape Province, South Africa: a qualitative study

Abstract: ObjectivesThe aim of this study was to explore and understand women's pathways to breast cancer diagnosis and factors influencing this journey.Design and settingIndepth interviews were conducted with clients at a tertiary level breast cancer clinic in Cape Town, South Africa. A thematic analysis was performed underpinned by the theoretical concepts of the Model of Pathways to Treatment framework.Participants20 women were interviewed within 1 week of being diagnosed with breast cancer.ResultsThe average time be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
100
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 28 publications
14
100
1
2
Order By: Relevance
“…You don't want to live anymore.' (Patient 3) The association of breast cancer with death was reported in several studies from sub-Saharan Africa [18,27]. It also clearly came up in the discussions with the women in the communities, but some women were aware that there are long-term survivors.…”
Section: Treatment Interval: From Diagnosis To Start Of Treatmentmentioning
confidence: 95%
See 4 more Smart Citations
“…You don't want to live anymore.' (Patient 3) The association of breast cancer with death was reported in several studies from sub-Saharan Africa [18,27]. It also clearly came up in the discussions with the women in the communities, but some women were aware that there are long-term survivors.…”
Section: Treatment Interval: From Diagnosis To Start Of Treatmentmentioning
confidence: 95%
“…(Patient 7) Women in the community highlighted their mistrust in health care workers: they have no knowledge nowadays, make wrong diagnoses, and often prescribe medicine that does not help. Other studies have also reported problems of wrong diagnosis and treatment [18,19] among breast cancer patients in sub-Saharan Africa.…”
Section: Diagnostic Interval: From First Health Seeking To Diagnosismentioning
confidence: 98%
See 3 more Smart Citations